Nanotechnology with application in air purification: adsorption of Hazardous gases onto metalorganic frameworks - Oviedo, Leandro Rodrigues; Druzian, Daniel Moro; Dalla Nora, Lissandro Dorneles; Da Silva, William Leonardo (Disciplinarum Scientia | Naturais e Tecnológicas, 2023)
Among the environmental problems generated from anthropogenic activities, the atmospheric pollution is of the most concern due to the great risks to society and environment. This pollution is directly related to the particulate matter and the hazardous industrial gases and vapors emitted to air. Thus, some technologies like adsorption are characterized as efficient and relatively low-cost technology to ameliorate this problem, in which metal-organic frameworks (MOFs) nanoadsorbents are used. Thus, this review aims to report the main advances in hazardous gases adsorption research area using MOFs and to understanding the adsorption mechanisms. From this study, 51 scientific papers were found involving the application of MOFs, confirming their potential in the air purification. Although MOFs are more advantageous than conventional nanoadsorbents (organic/inorganic one), mainly due to the high specific surface area, thermal/chemical stabilities, their occurrence in Brazil is quite low once few works are reported in Brazilian literature.